Significados, concepções e experiências de enfermeiros da Estratégia Saúde da Família de Belo Horizonte frente ao abuso infantil: teorização sobre a não notificação - Larissa Fernandes Correia Gonzaga (2023)
Child abuse has been recognized as a complex and endemic social issue, and a public health problem among children and adolescents. Healthcare professionals play a pivotal role in addressing child abuse. However, the patterns observed in the actions of nurses when dealing with cases of child abuse suggest the existence of difficulties and barriers, suggesting a high prevalence of non-reporting behavior among these professionals. In this context, this study aimed at understanding the meanings, conceptions, and experiences of nurses from the Family Health Strategy (FHS) in Belo Horizonte regarding child abuse, as well as to construct a theory about non-reporting behavior. This is a qualitative study based on the methodological framework of Grounded Theory (GT) and the theoretical framework of Symbolic Interactionism (SI). The participants (nurses) were selected in an intentional manner, and the snowball technique was also used, which each interviewed professional indicated another to participate in the study, allowing for reference-based sampling. Fourteen intensive interviews were conducted with nurses working in the FHS of nine Health Centers in Belo Horizonte. Data collection and categorization occurred simultaneously according to GT, and four main categories emerged from the analysis process. The category "Conception of child abuse" suggests that nurses find it difficult to address this issue, as it is associated with the violation of children's rights. The category "Conception of reporting" revealed theoretical confusion among FHS nurses regarding the terms "reporting" and "denunciation," which may partly explain the non-reporting behavior. The category "Communication between professionals and support agencies" suggests that communication usually occurs through a social worker, and most participants perceived the social worker's actions as more effective than those of the child protective services. The category "Barriers and Facilitators" includes fear and high workload, which can jeopardize the identification and reporting of abuse. Training, and FHS meetings were identified as potential facilitators for reporting. By analyzing the connections between the emerging categories and their relationships, the "Theory of non-reporting behavior among nurses in the Family Health Strategy" was developed. Understanding nurses' experiences, conceptions, and behaviors regarding child abuse allowed for the identification of actions that still need to be taken to fulfill the purpose of reporting, as these professionals play a fundamental role in caring for children and combating child abuse.